2015
DOI: 10.1161/circulationaha.114.015156
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Percutaneous Coronary Intervention Appropriateness

Abstract: Background-It is unknown whether the appropriate use of percutaneous coronary intervention (PCI) has improved over time and whether trends in PCI appropriateness have been accompanied by changes in the use of PCI. Methods and Results-We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…3,7 Our findings are consistent with an analysis of PCI appropriateness in Washington State. 21 However, because the registry was not configured to characterize PCI appropriateness until July 2009, our analyses are limited to cases performed after the release of the Appropriate Use Criteria. As such we could not evaluate the impact of the Appropriate Use Criteria, and our findings are best considered a description of changes in patterns of care and procedural appropriateness over this period.…”
Section: Discussionmentioning
confidence: 99%
“…3,7 Our findings are consistent with an analysis of PCI appropriateness in Washington State. 21 However, because the registry was not configured to characterize PCI appropriateness until July 2009, our analyses are limited to cases performed after the release of the Appropriate Use Criteria. As such we could not evaluate the impact of the Appropriate Use Criteria, and our findings are best considered a description of changes in patterns of care and procedural appropriateness over this period.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Bradley and colleagues 6 in this issue of Circulation provides some insight into that question. Using data from the Washington State Clinical Outcomes Assessment Program, they examined temporal trends in the number of percutaneous coronary intervention (PCI) procedures performed, specifically the number of PCIs rated as inappropriate.…”
Section: Article See P 20mentioning
confidence: 99%
“…With regard to some hospitals showing trends that were contrary to general trends, Bradley et al assessed the appropriateness of PCIs performed in Washington State and noted that hospitals in the tertile with the least improvement in the proportion of inappropriate PCIs had a temporal increase in the proportion of inappropriate PCIs from 12% in 2010 to 20% in 2013 [9]. The authors suggested that additional qualitative studies on hospitals with increasing proportions of inappropriate PCIs may serve to validate the patient selection processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies have further examined the regional and hospital variations in the percentage of PCIs for nonacute indications [5, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation